Molecular Characterization of Fasciola Spp. Isolated From the Gallbladder of Infected Cattle in Duhok Province, Kurdistan Region Iraq - Mohammed, Ahmed B.; Mustafa, Awat; Issa, Araz R.; Mero, Wijdan M.S. (Science Journal of University of Zakho, 2016)
Fascioliasis caused by the liver flukes of the genus Fasciola is considered as the most significant Trematodes infection of ruminants in both temperate and tropical countries. In the present study fifty adult Fasciola flukes (Platyhelminthes: Trematoda: Digenia) were collected from the bile ducts and gallbladder of infected bovine hosts (cattle) slaughtered at Duhok abattoir, Kurdistan region, Iraq.  Genomic DNA extraction was performed using a Genomic DNA Extraction kit. ITS-1 and ITS-2 ribosomal DNA sequences have been used to characterize these liver flukes as a specific marker. The PCR products were separated by electrophoresis in 1.5% agarose gel, visualized by staining with ethidium bromide, and photographed. ITS-2 marker for F. hepatica was amplified successfully and the length of produced band for ITS-2 was 330 bp. The present study is the first trail for molecular characterization of F. hepatica in cattle in Duhok, Kurdistan Region, Iraq  using the ITS-2 rDNA as a reliable genetic marker.
Keywords: Fasciola hepatica; Cattle; ITS-2 ribosomal DNA; Duhok